Potential of Piperaceae Plants as Antibacterial against Staphylococcus aureus and Escherichia coli: A Review - Magdalena, Hottria; Fajrina, Anzharni; Eriadi, Aried; Asra, Ridho (Asian Journal of Pharmaceutical Research and Development, 2021)
Background: Infectious disease was one of the most common health problems in developing countries which are caused by microorganism, such as bacteria. Piper (Piperaceae) was a medicinal plant that has potential as an antibacterial. Some plants of the piperaceae family have antibacterial activity against Escherichia coli and Staphylococcus aureus, such as Piper cubeba, Piper nigrum, Piper betle, Piper crocatum, Piperomia pellucida, Piper longum, Piper sarmentosum, and Piper aduncum. Purpose: This article described plant of the Piperaceae family that has antibacterial potential. This article reviewed the study of the antibacterial potential of the Piperaceae plant from various articles. Data source: The database sources used include Google Scholar, Science Direct, and Media Published from 2010 to 2021. Conclusion: It carried out by reviewing several libraries such as indexed national journals, international journals, and scientific articles regarding the potential of the Piperaceae plants as antibacterial against Staphylococcus aureus and Escherichia coli. The antibacterial activity of the Piperaceae plant originated from secondary metabolites of these plants including alkaloids, tannins, saponins, phenolic compounds, and flavonoids.